2019
DOI: 10.3390/nu11030690
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Physical Activity Levels during a Single Day on Energy Intake, Appetite, and Energy Balance: A Preliminary Study

Abstract: We aimed to investigate the effects of a wide range of daily physical activity (PA) levels on energy balance (EB), energy intake (EI), and appetite. Nine young men completed three different PA levels in a metabolic chamber in a random order: (1) no exercise (Low-PA); (2) 25 min walking seven times (Mid-PA); and (3) 25 min running seven times (High-PA) within a 24 h period. Interval exercise (25 min exercise and 35 min rest) was performed three times in the morning and four times in the afternoon. The exercise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
1
5
1
Order By: Relevance
“…When energy intake is more than energy expenditure; that is, when energy balance shifts positively, weight gain begins (Mahan & Raymond, 2016). Hatamoto et al concluded in their study that significantly different daily physical activity did not energy intake (Hatamoto et al, 2019). In this study, no significant difference was found between physically active and inactive men in terms of energy expenditure, while physically inactive women had statistically significantly higher energy intake compared to active women (p < 0.05).…”
Section: Discussioncontrasting
confidence: 56%
“…When energy intake is more than energy expenditure; that is, when energy balance shifts positively, weight gain begins (Mahan & Raymond, 2016). Hatamoto et al concluded in their study that significantly different daily physical activity did not energy intake (Hatamoto et al, 2019). In this study, no significant difference was found between physically active and inactive men in terms of energy expenditure, while physically inactive women had statistically significantly higher energy intake compared to active women (p < 0.05).…”
Section: Discussioncontrasting
confidence: 56%
“…Some epidemiological studies indicated a U‐ 35 or J‐shaped 36 relationship between the PA level and EI, and the lowest PA groups have higher EI and body weight. Conversely, an experimental study using metabolic chambers has shown that EI does not change, but energy balance differs at different levels of PA 37 . These data imply that EI is not automatically matched to the PA level.…”
Section: Discussionmentioning
confidence: 91%
“…Energy balance is important not only for EI but also for energy expenditure, including PA. [35][36][37] Some epidemiological studies indicated a U- 35 or J-shaped 36 relationship between the PA level and EI, and the lowest PA groups have higher EI and body weight. Conversely, an experimental study using metabolic chambers has shown that EI does not change, but energy balance differs at different levels of PA. 37 These data imply that EI is not automatically matched to the PA level. Although we adjusted for self-reported PA as a confounder, we could not evaluate the relationship between energy balance and mortality risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible reason for these declines could be decreased physical activity. In China, although leisure-time physical activity have generally increased since 2000 ( 19 ), total physical activity have dropped sharply from 1991 to 2009 ( 20 ), and classical literatures showed a J-shaped relationship between physical activity and energy intake ( 21 , 22 ). However, physical activity was also inversely related to incident diabetes ( 23 ).…”
Section: Discussionmentioning
confidence: 99%